Hepatitis B serological markers and plasma DNA concentrations. (15th May 2017) - Price, Huw; Dunn, David; Zachary, Tamale; Vudriko, Tobias; Chirara, Michael; Kityo, Cissy; Munderi, Paula; Spyer, Moira; Hakim, James; Gilks, Charles; Kaleebu, Pontiano; Pillay, Deenan; et al.
Abstract : Objectives: To examine hepatitis B (HBV) serological markers and plasma DNA concentrations in a large group of untreated HBV/HIV-coinfected individuals in two sub-Saharan settings. Design: Baseline analysis of a randomized controlled trial. Methods: DART was a large trial of treatment monitoring practices in HIV-infected adults with advanced disease starting antiretroviral therapy at centres in Kampala or Entebbe, Uganda ( n = 2317) and Harare, Zimbabwe ( n = 999). HBV serological markers [antibody to HBV core antigen, HBV surface antigen (HBsAg), antibody to HBV surface antigen, HBV 'e' antigen (HBeAg), and antibody to hepatitis B 'e' antigen] and plasma HBV DNA viral load were measured retrospectively on stored baseline samples. Logistic regression was used to examine associations with baseline demographic and clinical factors. Results: The rate of HBsAg positivity was significantly higher in Zimbabwe than Uganda (12.2 vs. 7.7%, adjusted odds ratio = 1.54, P < 0.001) despite a similar prevalence of antibody to HBV core antigen (56.3 vs. 52.4%) in the two settings. Overall, HBsAg positivity was associated with male sex (adjusted odds ratio = 1.54, P < 0.001) but not with age, WHO disease stage, or CD4 + cell count. HBeAg was detected among 37% of HBsAg-positive patients, with higher rates among those with advanced WHO stage ( P = 0.02). Also in HBsAg-positive patients, HBV DNA was undetectable in 21%, detectable but below the level of quantification in 14%, and quantifiable in 65%. A total of 96% of HBeAg-positive and 70% of HBeAg-negative patients had detectable HBV DNA; 92 and 28% of patients, respectively, had HBV DNA viral load more than 2000 IU/ml. Conclusion: High rates of HBV coinfection were observed, highlighting the importance of ensuring that coinfected patients receive an antiretroviral regimen, whether first-line or not, that is active against both viruses. Abstract : Supplemental Digital Content is available in the text